2021
DOI: 10.3390/nu13041384
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Related Stress and Anxiety, Body Mass Index, Eating Disorder Symptomatology, and Body Image in Women from Poland: A Cluster Analysis Approach

Abstract: To limit the spread of the novel coronavirus (COVID-19), many countries have introduced mandated lockdown or social distancing measures. Although these measures may be successful against COVID-19 transmission, the pandemic and attendant restrictions are a source of chronic and severe stress and anxiety which may contribute to the emergence or worsening of symptoms of eating disorders and the development of negative body image. Therefore, in this study, we aimed to: (1) classify different conditions associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 48 publications
2
25
0
1
Order By: Relevance
“…Moreover, children with greater generalized, separation, and social anxiety symptoms reported greater body image dissatisfaction, which was in line with our hypothesis. These results are also in line with two recent studies on the impact of COVID-19-related anxiety on adults’ body image dissatisfaction [ 18 , 19 ] and support the notion that these links extend to children as well.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, children with greater generalized, separation, and social anxiety symptoms reported greater body image dissatisfaction, which was in line with our hypothesis. These results are also in line with two recent studies on the impact of COVID-19-related anxiety on adults’ body image dissatisfaction [ 18 , 19 ] and support the notion that these links extend to children as well.…”
Section: Discussionsupporting
confidence: 92%
“…Generalized anxiety , on its part, represents excessive worry and may lead individuals to rely more on the acceptance of others and to be more sensitive to unrealistic societal standards of health and weight [ 17 ]. To date, two cross-sectional studies have reported that greater COVID-19-related anxiety was associated with greater body image dissatisfaction in adults [ 18 , 19 ]. However, it is unclear whether children’s body image dissatisfaction was impacted by COVID-19-related anxiety and trauma symptoms.…”
mentioning
confidence: 99%
“…The fourth theme concerned pandemic‐related correlates of symptom severity. Fifteen studies investigated this theme; 14 studies investigated cross‐sectional relationships ( n s = 43–5,738; Castellini et al, 2020 ; Christensen et al, 2021 ; Czepczor‐Bernat et al, 2021 ; De Pasquale et al, 2021 ; Flaudias et al, 2020 ; Haddad et al, 2020 ; Jordan et al, 2021 ; Machado et al, 2020 ; Racine et al, 2021 ; Scharmer et al, 2020 ; Schlegl, Maier, et al, 2020 ; Schlegl, Meule, et al, 2020 ; Simone et al, 2021 ; Thompson & Bardone‐Cone, 2021 ) and one pilot study of 15 individuals with bulimia nervosa assessed prospective relationships using an experience sampling design (Leenaerts et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Second, several studies appeared to have omitted reporting non‐significant relationships. Seven studies reported significant positive relationships between COVID‐19‐related fears, anxiety, and stress with various cognitive and behavioral symptoms of eating disorders (Castellini et al, 2020 ; Czepczor‐Bernat et al, 2021 ; De Pasquale et al, 2021 ; Flaudias et al, 2020 ; Haddad et al, 2020 ; Machado et al, 2020 ; Scharmer et al, 2020 ). Two studies each found eating disorder symptoms to be significantly and positively correlated with food insecurity (Christensen et al, 2021 ; Simone et al, 2021 ) and financial difficulties (Haddad et al, 2020 ; Simone et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The situation has given rise to concerns for one’s own health [ 4 , 5 ], and many reports show how COVID-19 and restrictions related to it can affect both psyche and soma [ 2 , 6 , 7 , 8 , 9 , 10 , 11 ]. Within this context, research findings have also been published on, inter alia: (a) changes in eating behavior [ 12 , 13 , 14 ]; (b) the relationships between COVID-19-related stress, disordered eating (e.g., emotional overeating) [ 15 , 16 , 17 ], symptoms of eating disorders, and negative body image [ 18 , 19 , 20 , 21 , 22 ]; (c) the functioning of people who are overweight and have possible changes in body weight [ 13 , 23 ].…”
Section: Introductionmentioning
confidence: 99%